Renal dysfunction is associated with lower odds of home discharge for patients with stroke. Issue 8 (17th November 2021) - Wang, I-Kuan; Yu, Tung-Min; Yen, Tzung-Hai; Chiu, Lu-Ting; Lien, Li-Ming; Sun, Yu; Wei, Cheng-Yu; Hsu, Kai-Cheng; Lai, Ping-Chin; Li, Chi-Yuan; Sung, Fung-Chang; Hsu, Chung Y.
ABSTRACT: Objectives: Studies on the association of estimated glomerular filtration rate (eGFR) levels with hospital discharge disposition after stroke are limited with inconsistent results. This study investigated the odds of home discharge with eGFR levels at admission for patients with stroke using the Taiwan Stroke Registry (TSR) data. Methods: From the TSR database, a total of 51, 338 stroke patients from 2006 to 2015 were categorized into five groups based on eGFR levels at admission. The proportion of home discharge by the eGFR levels was calculated and logistic regression analysis was used to estimate the related odds ratio (OR) and 95% confidence interval. Results: Near 85% of stroke patients were discharged to home. The proportion of home discharges decreased as the eGFR level declined. Compared to patients with eGFR ≥90 mL/min/1.73 m 2, the adjusted ORs of home discharge were 0.91, 0.85, 0.63, 0.56 for patients with eGFR 60–89, eGFR 30–59, eGFR 15–29, and eGFR < 15 mL/min/1.73 m 2 or on dialysis, respectively, in a graded relationship. The trends were consistent in the ischemic stroke and hemorrhagic stroke patients. The areas under the receiver operating characteristic curve for all stroke patients, ischemic stroke patients, and hemorrhagic stroke patients were 0.801, 0799, 0.815, respectively. Conclusion: The odds of home discharge for stroke patients decreased with a significant independent graded association with declining eGFR levels. Renal function could predict home discharge after stroke.